Mean annual temperature and carbon availability respectively controlled the contributions of bacterial and fungal residues to organic carbon accumulation in topsoil across China's forests - Xuechao Zhao; Peng Tian; Shengen Liu; Pan Yin; Zhaolin Sun; Qingkui Wang (Global Ecology and Biogeography, 2023)
Aim Soil organic carbon (SOC) stabilization has become an important topic in recent years in the context of global climate change. Microbial residues represent a significant component of stabilized SOC pools. However, spatial variations in the contributions of bacterial and fungal residues to SOC and their determinants at a continental scale remain poorly understood. We aimed to evaluate the spatial variations and controls of the contributions of microbial residues to SOC in forest topsoil. Location North–south transect in eastern China. Time period 2014. Major taxa studied Forest ecosystems. Methods A total of 195 surface (0–10 cm) soils were sampled from 28 forest sites across tropical and boreal forests in eastern China from July to August to assess how biotic and abiotic factors govern the geographic patterns of the contributions of soil microbial residues (indicated by amino sugars) to SOC. Results Fungal residues (30.0%) had a greater average contribution to SOC than bacterial residues (15.5%). The contributions of bacterial (CBR) and total microbial residues (CMR) to SOC showed negative latitudinal patterns and were positively correlated with mean annual temperature (MAT). In contrast, the contribution of fungal residues to SOC (CFR) showed no clear geographic or climatic patterns. On average, the CBR (9.7%), CFR (21.1%) and CMR (30.8%) were lower in boreal forests than in other biome forests. SOC concentration negatively mediated CBR, CFR and CMR. The piecewise structural equation model results showed that MAT was the primary driver of the geographic pattern of CBR, whereas SOC and soil carbon : nitrogen ratio were more directly associated with the CFR. Additionally, plant factors and microbial properties (i.e., microbial biomass and composition) played relatively little roles in regulating CBR, CFR and CMR. Main conclusions These findings advance the current knowledge of the different geographic patterns of CBR and CFR regulated by different potential mechanisms in forest ecosystems. This highlights that the dynamics of microbial residues could potentially have unexpected consequences for topsoil SOC stocks under climate change.